Las argucias del concepto de integración: una exploración por el paisaje Europeo - Araujo, Sandra Gil (Oñati Socio-Legal Series, 2011)
This article argues that immigrant integration policies be viewed as tools for construction of the national. It does so by illuminating the links between debates about immigrant integration and ways of imagining the nation and national identity. To this end, the article analyzes the political and socioeconomic context in which the presence of immigrants from non European Union countries is defined as a problem of integration. It centers on three traditional immigration receiving countries after World War II - the United Kingdom, France, and the Netherlands - and Spain, a newer destination country of the post-Fordist era. The study shows commonalities in wording, categorizations, and problem definition across these countries in debates about non European Union immigrants without ignoring state particularities. Above all, it demonstrates the persistence of "integration" as a term to reference relationships between European societies and the non-European immigrant population.